Exploring Dance Movement Therapy and Creative Embodiment: A Scoping Review on Interdisciplinary Exploration in Arts and Education - Tiara FL, Rani; Rita Milyartini; Juju Masunah (Journal of Practice Learning and Educational Development, 2026)
This scoping review explores the interdisciplinary applications of Dance Movement Therapy (DMT) and creative embodiment within arts and education contexts. The study aims to map how embodied practices, movement exploration, and experiential learning contribute to students’ emotional, cognitive, and social development. Following the PRISMA-ScR framework, ten peer-reviewed articles published between 2020 and 2025 were systematically analyzed across databases such as Scopus, Taylor & Francis, Frontiers, and Google Scholar. The findings reveal four thematic areas: (1) the therapeutic potential of dance in enhancing well-being and self-expression, (2) movement exploration as a framework for collaborative and reflective learning, (3) cultural and technological innovations in dance pedagogy, and (4) the integration of embodied practices in interdisciplinary education. These studies highlight DMT’s significance as both an artistic and pedagogical approach that bridges creativity, emotional awareness, and inclusive learning. The review concludes that incorporating dance and embodiment in education promotes not only aesthetic appreciation but also psychosocial growth and intercultural understanding. Further research is recommended to expand empirical evidence and strengthen the implementation of DMT within educational systems.